Applications of Various Types of Circuit Breakers in Electrical Power Systems: A Review - Obi, P. I.; Ezeonye , C. S.; Amako, E. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
This paper presents a review on the applications of various types of circuit breakers (CB) used in electric power transmission and distribution. Circuit breakers are majorly classified under direct current (DC) or alternating current (AC) system. It shows that the most suitable way of classifying circuit breakers is on the level of voltage rating which is broadly grouped under direct current (DC) or alternating current (AC) circuit breakers. However, reviewed literatures did not clearly distinguish the respective applications of the different types of circuit breakers as applied to DC and AC power network. The DC circuit breakers which comprises of mechanical, solid-state and hybrid breakers are mostly applied in domestic and industrial applications that employ the use of direct current (DC) especially in high voltage direct current (HVDC) network system for the protection of electrical devices. AC circuit breakers are grouped in high voltage and low voltage forms. The low voltage CB comprises of miniature and molded case circuit breakers used majorly in domestic and commercial installations. The high voltage circuit breakers are further subdivided into oil and oil-less forms. The oil-less CB is made up air, vacuum and sulphur hexafluoride (SF6) circuit breakers. These high voltage circuit breakers are majorly applied in high voltage and extra high voltage transmission systems for protection of power system equipment and electrical machines.